Isolation of Nanocellulose Fibers (NCF) from cocoa pod (Theobroma cacao L.) via chemical treatment combined with ultrasonication - Jimat, Dzun Noraini; Syed Putra, Sharifah Shahira; Jamal, Parveen; Wan Nawawi, Wan Mohd Fazli (Springer, Singapore, 2020)
Cellulose is commonly known for its uses in the production of products and materials due to its fascinating structure and properties, and it is also an almost unlimited organic polymeric raw material. In this research, cellulose nanoﬁbers (CNF) from cocoa pod husks (Theobroma cacao L.) CPH is extracted using alkaline and minimal concentration of sulfuric acid and further disintegrated with ultrason-ication. The FESEM result proved that ﬁbers with nano-dimension; diameter of 20–30 nm were observed. Based on FTIR spectrum result, it is shown that the pres-ence of peaks of around 1170–1046 and 890–670 cm−1 is associated with the C–O stretching and C–H bend vibrations of the cellulose pyranose ring skeletal. The range of size distribution of CNF–CPH is within 200–400 nm as shown in the particle size analysis.